Dampak Struktur Pendanaan, Periode Pengembalian dan Tingkat Inflasi terhadap Proyeksi Arus Kas Proyek - Trenda Indri Ardianti; Nanik Dwi Siswati; Berliana Indah Kusumaningrum; Putu Rena Suci Novalita; Maria Yovita R.Pandin (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine the influence of capital structure, payback period, and inflation rate on project cash flow projections in cosmetic manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. A quantitative approach was employed using multiple linear regression analysis. The data were obtained from audited annual financial reports, serving as secondary data sources. The findings reveal that, simultaneously, the three independent variables significantly affect project cash flow projections. However, when assessed individually, only capital structure demonstrates a statistically significant impact, while payback period and inflation rate do not show meaningful influence. These results highlight the importance of optimizing capital structure to maintain cash flow stability, and suggest that investment evaluations should incorporate broader financial indicators to account for macroeconomic dynamics.